Influence of Geometric Structure, Convection, and Eddy on Sound Propagation in Acoustic Metamaterials with Turbulent Flow - PAK, Myong Chol; KIM, Kwang-Il; PAK, Hak Chol; HONG, Kwon Ryong (Archives of Acoustics, 2021)
The problem of reducing noise in transportation is an important research field to prevent accidents and to provide a civilised environment for people. A material that has recently attracted attention in research to reduce noise is acoustic metamaterial, and most of the research projects so far have been limited to the case of static media without flow. We have studied the sound transmission properties of the acoustic metamaterials with turbulent flow to develop the acoustic metamaterials that are used in transportation. In this paper, the effects of geometrical structure, convection, and eddy on sound propagation in the acoustic metamaterials with turbulent flow are investigated, and the relationships between them are analysed. The effects of convection and eddy reduce the resonant strength of the sound transmission loss resulting from the unique geometry of the acoustic metamaterials, but move the resonant frequencies to opposite directions. In addition, when the convective effect and the eddy effect of the airflow, as well as the intrinsic interaction effect generated from the unique geometrical structure of the acoustic metamaterials cannot be ignored, they exhibit competition phenomena with each other, resulting in a widening of the resonance peak. As a result, these three effects cause the shift of the resonance frequency of the sound transmission loss and the widening of the resonance peak. The results of this study show that even in the case of turbulent flow, the metamaterials can be used for transportation by properly controlling its geometric size and shape.